2020
DOI: 10.3892/ol.2020.11341
|View full text |Cite
|
Sign up to set email alerts
|

Simple scoring system for prediction of hepatocellular carcinoma occurrence after hepatitis C virus eradication by direct‑acting antiviral treatment: All Kagawa Liver Disease Group Study

Abstract: Direct acting antivirals (DAA) have recently been developed to treat patients with hepatitis C virus (HCV) infection, and interferon-free DAA treatment has improved the cure rate of patients. However, the occurrence rate of hepatocellular carcinoma (HCC) following HCV eradication remains unknown. Therefore, the present study aimed to identify predictors of HCC occurrence following DAA treatment. Among 1,454 patients infected with HCV, 1,088 patients who achieved sustained virologic response and who had no hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 40 publications
4
28
0
1
Order By: Relevance
“…The 1-, 2-, 3-, and 4-year incidence rates of HCC for the low-score group (0 points or 1 point) were 0.7%, 2.2%, 3.1%, and 3.1% compared to 12.5%, 15.2%, 33.9%, and 41.2%, respectively, in the high-score group (2 or 3 points). Previous studies reported the stratification of HCC incidence by FIB-4 scores and AFP levels after SVR and by scores composed of patient sex and age, with and without cirrhosis [11,12]. On the other hand, the score established in this study is useful for patients with compensated cirrhosis who still have an absolute risk of residual HCC.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The 1-, 2-, 3-, and 4-year incidence rates of HCC for the low-score group (0 points or 1 point) were 0.7%, 2.2%, 3.1%, and 3.1% compared to 12.5%, 15.2%, 33.9%, and 41.2%, respectively, in the high-score group (2 or 3 points). Previous studies reported the stratification of HCC incidence by FIB-4 scores and AFP levels after SVR and by scores composed of patient sex and age, with and without cirrhosis [11,12]. On the other hand, the score established in this study is useful for patients with compensated cirrhosis who still have an absolute risk of residual HCC.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, another study demonstrated that in patients without cirrhosis, higher FIB-4 scores, the presence of DM, and alcohol use were risk factors for developing HCC after DAA treatment [3]. In addition, recent studies reported that male sex, increased FIB-4 scores, decreased ALB levels, older age, and increased AFP levels were independent risk factors identified by multivariate analysis [11][12][13]. In the present study, a longterm observation period of more than 3 years was used, and the HCC risk factors after HCV eradication were identified in patients with compensated cirrhosis or without cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many risk factors, including primary hepatitis C virus, hepatitis B virus, smoking, cirrhosis and obesity, are involved in HCC. [ 21 , 22 ] The gut microbiota is involved in protection against or promotion of different diseases, including various cancers. The gut microbiota composition differs in several diseases, including obesity, inflammatory bowel disease, and hepatocellular carcinoma (HCC), suggesting a distinct intestinal metabolism and immune response in each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tani et al [ 39 ], who followed for 24 months 1084 HCV patients who achieved an SVR, showed that the incidence of HCC was 0.61%, 1.88%, 2.82% and 3.71% at 6, 12, 18 and 24 months after treatment with DAAs, respectively. Furthermore, they identified age and alfa-fetoprotein levels as the independent predictors of HCC occurrence.…”
Section: Occurrence Of Hcc After Treatment With Daasmentioning
confidence: 99%
“…Several studies have shown that the male sex, diabetes and elevated serum alpha-fetoprotein levels before and after DAAs treatment are significant predictors of the onset or recurrence of HCC [ 34 , 39 , 66 , 67 , 102 ].…”
Section: Predictive Factors Of Hcc Appearance or Recurrencementioning
confidence: 99%